2014
DOI: 10.1016/j.jctb.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Vertex-disjoint directed and undirected cycles in general digraphs

Abstract: 6The dicycle transversal number τ (D) of a digraph D is the minimum 7 size of a dicycle transversal of D, i. e. a set T ⊆ V (D) such that D − T 8 is acyclic. We study the following problem: Given a digraph D, decide 9 if there is a dicycle B in D and a cycle C in its underlying undirected 10 graph UG(D) such that V (B) ∩ V (C) = ∅. It is known that there is a 11 polynomial time algorithm for this problem when restricted to strongly 12 connected graphs, which actually finds B, C if they exist. We generalize 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…As an example, in [2,3] the problem of deciding for a digraph D the existence of a directed cycle C in D and a cycle C ′ in U G(D) which are vertex disjoint was studied. It was shown that this problem is polynomially decidable for the class of digraphs with a bounded number of cycle transversals of size 1 (vertices whose removal eliminates all directed cycles) and N P-complete if we allow arbitrarily many transversal vertices.…”
Section: Problem 13 Semi-directed 2-factors Of Bipartite Digraphsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, in [2,3] the problem of deciding for a digraph D the existence of a directed cycle C in D and a cycle C ′ in U G(D) which are vertex disjoint was studied. It was shown that this problem is polynomially decidable for the class of digraphs with a bounded number of cycle transversals of size 1 (vertices whose removal eliminates all directed cycles) and N P-complete if we allow arbitrarily many transversal vertices.…”
Section: Problem 13 Semi-directed 2-factors Of Bipartite Digraphsmentioning
confidence: 99%
“…It follows from (B.2) and (B.3) that B 3 = B ′′ [W \ {w 1 , w 2 } ∪ V 2 \ X] and B 4 = B ′′ [V 1 \ W ∪ X \ {x 1 , x 2 }] are balanced bipartite graphs with parts of size n/2 − 1 where each vertex has degree at least n/2 − 2. Hence, B 3 has a perfect matchingM 3 and B 4 has a perfect matchingM 4 . ThenM 3 ∪M 4 ∪ {x 1 w 1 , x 2 w 2 } is a perfect matching in B ′′ , contradicting that Problem 1.2 has a negative answer.…”
Section: A Polynomial Instance Of Problem 12mentioning
confidence: 99%
“…Since a digraph with at least two nontrivial strong components of size greater than one has two disjoint dicycles and the dicyle transversal number of any digraph D is the sum of the dicycle transversal numbers of its strong components, we may assume that D has precisely one nontrivial strong component D that is a no‐instance of Problem and since every digraph D with τ(D)3 is a yes‐instance of Problem and hence also of Problem we can assume that τ(D){1,2}.…”
Section: The Case Of Nonstrong Digraphsmentioning
confidence: 99%
“…In we completely characterized the complexity of the following problem that can be seen as lying in‐between the two problems of two disjoint cycles in a graph and two disjoint dicycles in a digraph. Problem Given a digraph D , decide if there is a dicycle B in D and a cycle C in UG(D) with V(B)V(C)=.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation